Could Intermediate Screw in Thoracolumbar Fracture Fixation Save Motion Levels? Comparative Study between Long-Segment and Short-Segment with Intermediate Screw Fixation - Tarek ElHewala (Egyptian Spine Association, 2019)
Background Data: Thoracolumbar fractures are commonly managed by posterior pedicle screw fixation. Controversy about the number of levels involved in the fixation remains as the stability of the short-segment fixation remains questionable. Recently, it has been shown that application of intermediate screw in the fractured vertebra improves the biomechanical stability of the short-segment construct. Purpose: To compare the outcome of long-segment fixation (LSF) versus short-segment fixation with intermediate screws (SSFIS) in the management of the thoracolumbar burst fractures. Study Design: A prospective, nonrandomized clinical controlled trial. Patients and Methods: Fifty patients with thoracolumbar burst fracture (T11-L2) types A3 and A4 AOSpine classification with a Thoracolumbar Injury Classification and Severity (TLICS) scale of more than 4 were treated between 2009 and 2014 with posterior pedicle screw fixation. Patients were divided into two groups according to the number of instrumented levels. Group 1 included 25 patients treated with LSF (two levels above and two levels below the fractured level) while Group 2 included 25 patients treated by SSFIS (one level above and one level below with 2 intermediate screws in the fractured level). The patients were evaluated for local kyphotic angle (LKA) correction and maintenance, anterior vertebral body height (AVH) compression, and Visual Analogue Scale (VAS) for back pain and treatment related complications. Construct failure was defined as screw pullout or instrument breakage. Results: The two groups were similar with regard to age, sex, fractured levels, fracture type, TLICS score, preoperative local kyphotic angle, and anterior vertebral body height compression. Postoperative correction of the local vertebral compression assessed with LKA and AVH significantly improved in both groups compared to the preoperative degree. There was no significant difference in the two groups in early postoperative or follow-up regarding the degree of correction and its maintenance. No construct failure or major treatment related complication was encountered in both groups with significant reduction of VAS and ODI in both groups between early postoperative and late follow-up (13.5±2 months). Conclusion: Intermediate screw applied in the fractured level in management of thoracolumbar burst fracture improves the correction and maintenance of local kyphosis in short-segment fixation like long-segment construct with saving vertebral motion levels from being fixed. More randomized controlled and multicenter studies are needed to support these findings. (2019ESJ175)